Reduced Expression of Junctional Adhesion Molecule and Platelet/Endothelial Cell Adhesion Molecule-1 (CD31) at Human Vascular Endothelial Junctions by Cytokines Tumor Necrosis Factor-α Plus Interferon-γ Does Not Reduce Leukocyte Transmigration Under Flow - Shaw, Sunil K. (American Society for Investigative Pathology, 2001)
The combination of tumor necrosis factor (TNF)-α plus interferon (IFN)-γ has been shown previously to promote redistribution of platelet/endothelial cell adhesion molecule-1 (PECAM-1) (CD31), junctional adhesion molecule (JAM), and VE-cadherin away from lateral junctions of human umbilical vein endothelial cell monolayers. In parallel, neutrophil transmigration was significantly reduced. Because PECAM-1 and JAM have been implicated in leukocyte transmigration, the observed redistribution by cytokine activation was presumed to represent the mechanism causing decreased transmigration under static conditions. The current results confirm that culture of human umbilical vein endothelial cells with TNF-α plus IFN-γ caused a decrease in surface-expressed and junctional-localized JAM and PECAM-1, but did not cause decreased leukocyte transmigration in an in vitro flow assay. Furthermore, blocking monoclonal antibody to PECAM-1 still significantly reduced monocyte transmigration, demonstrating that it retains a functional role even though its levels were reduced and redistributed away from junctions, whereas a panel of monoclonal antibodies to JAM failed to reduce leukocyte transmigration. Given the alterations in junction protein location, permeability function was assessed. IFN-γ alone or TNF-α plus IFN-γ significantly increased permeability, but TNF-α alone did not, suggesting lack of correlation between transmigration and loss of permeability. In conclusion, cytokine activation induced loss and redistribution of PECAM-1 and JAM away from lateral junctions, but per se does not negatively regulate either neutrophil or monocyte transmigration under flow.